PENGARUH MASASE KAKI DENGAN MINYAK SEREH WANGI TERHADAP PENURUNAN TEKANAN DARAH HIPERTENSI LANSIA DI KOTA PEKALONGAN - Indar Widowati; Afiyah Sri Harnany; Zaenal Amirudin, Rr.Sri; Rr. Sri Sejati (LPPM Universitas Pekalongan, 2014)
Increased life expectancy, causes the increase of the elderly population that have an impact on the shift of disease pattern from infectious diseases to degenerative diseases such as hypertension . Treatment of hypertension can be done in a way that is pharmacological with anti- hypertensive drugs or non- pharmacological is with lifestyle modification or it could be a combination of both. Therapeutic massage is one of the non- pharmacological therapies that can reduce hypertension . Massage techniques at some point to remove the blockage in the blood so that blood and energy flow in the body back smoothly . This study aims to determine the effect of foot massage with citronella oil to decrease blood pressure of elderly hypertensive patients . This type of research is the study randomized pre - post test design with control